2012
DOI: 10.1097/dcr.0b013e31826d5cb5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of High-Grade Anal Intraepithelial Neoplasia With Infrared Coagulation in a Primary Care Population of HIV-Infected Men and Women

Abstract: Infrared coagulation is an effective treatment for high-grade anal intraepithelial neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 30 publications
2
32
1
2
Order By: Relevance
“…Nonetheless, a number of observational studies have suggested that IRC ablation of HSIL in HIV-infected patients is accompanied by frequent recurrence requiring re-treatment, while the probability of cure of individual HSIL lesions is high [34][41]. In the absence of randomized controlled trials, it is not clear that IRC ablation reduces progression to IAC [42].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a number of observational studies have suggested that IRC ablation of HSIL in HIV-infected patients is accompanied by frequent recurrence requiring re-treatment, while the probability of cure of individual HSIL lesions is high [34][41]. In the absence of randomized controlled trials, it is not clear that IRC ablation reduces progression to IAC [42].…”
Section: Discussionmentioning
confidence: 99%
“…He felt that infrared coagulation ablation, because of its limited depth of destruction and hemostatic effects, could be safely performed on outpatients by nonsurgeons (personal communication, Stephen E Goldstone). Subsequent to his initial description, there have been many reports of infrared coagulation ablation of AIN 4247…”
Section: Infrared Coagulation Of Ainmentioning
confidence: 99%
“…This allows for local treatment without damaging deeper tissues. These characteristics have allowed infrared coagulation to be used successfully by nonsurgeons 4345,47. After infrared coagulation, most patients are able to continue their usual activities with simple analgesics and a high fiber diet after 1–2 days of oral narcotics and tub soaks.…”
Section: Infrared Coagulation Of Ainmentioning
confidence: 99%
See 2 more Smart Citations